Analisis Strategi Bidang Perdagangan PT.Petrokopindo Cipta Selaras dalam Upaya Meningkatkan Performa Penjualan - Aulia Life Rahma Putri; Lia Nirawati (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The research aims to analyze the trading strategies implemented by PT. Petrokopindo Cipta Selaras to enhance sales performance. The study employs a quantitative descriptive method, utilizing data collection techniques such as interviews, observations, data processing, and documentation. The collected data is analyzed thematically to identify the strategies used by the company to improve operational performance and customer satisfaction.Based on the analysis of data from PT. Petrokopindo Cipta Selaras for the period 2021-2023, it is observed that Market Share, Market Growth, and Revenue Growth have increased based on the calculation of revenue. The results of the hypothesis test indicate that Market Share and Market Growth have a significant impact on Revenue Growth. It is expected that the research findings will provide a deep understanding of PT. Petrokopindo Cipta Selaras's ability to effectively understand and respond to consumer preferences. This understanding will serve as a foundation for formulating strategic analysis to enhance sales performance, helping the company to maintain and increase market share, and strengthen its reputation as a trusted provider of logistics solutions, trading services, and industrial needs.